Thermal chaos of quantum-corrected-AdS black hole in the extended phase space - Lei You; Rui-Bo Wang; Yu-Cheng Tang; Jian-Bo Deng; Xian-Ru Hu (European Physical Journal C: Particles and Fields)
Abstract We briefly analyzed the equation of state and critical points of the quantum-corrected-AdS black hole and used the Melnikov method to study its thermal chaotic behavior in the extended phase space of flat, closed, and open universes. The results show that the black hole’s thermodynamic behavior is similar to that of the Van der Waals system. Although the critical ratios at the critical points in the three types of universes differ, they are all independent of the quantum correction parameter. Only an open universe can attain the critical ratio of $$\frac{3}{8}$$ 3 8 corresponding to the Van der Waals system, while in the other two universes, the critical ratio is always greater than this value. For chaos, time perturbations will lead to chaotic behavior when their amplitude exceeds a critical value that depends on the quantum correction parameter and the radius of the dust sphere in the FRW model. Based on this, we found that the chaotic behavior of the black hole varies across different universes depending on the quantum correction parameter, but this parameter always makes chaos more likely. Using the value of the quantum correction parameter determined by Meissner, chaos is always more difficult to occur in an open universe compared to the other two types of universes. Which universe is most prone to chaos depends on the radius of the dust sphere. Finally, chaotic behavior is always present under spatial perturbations.